"How do I keep this live in my mind?" Allied Health Professionals' perspectives of barriers and enablers to implementing good clinical practice principles in research: a qualitative exploration - Rachel Wenke; Shelley Roberts; Rebecca Angus; Maame Amma Owusu; Kelly Weir (BMC, 2023)
Abstract Background Allied health professionals (AHPs) engaged in research are expected to comply with Good Clinical Practice (GCP) principles to protect participant safety and wellbeing and enhance data integrity. Currently, few studies have explored health professionals' perceptions of implementing and adhering to GCP principles in research with none of these including AHPs. Such knowledge is vital to guide future interventions to increase adherence to GCP principles. This study aimed to identify the barriers and enablers AHPs experience when applying GCP principles to research conduct in a public hospital and health service, as well as their perceived support needs. Methods The study used a qualitative descriptive study approach guided by behaviour change theory. AHPs currently undertaking ethically approved research within a public health service in Queensland, Australia were interviewed to explore barriers and enablers to adherence to GCP principles and support needs, with interview questions guided by the Theoretical Domains Framework (TDF). The TDF was chosen as it allows for a systematic understanding of factors influencing implementation of a specific behaviour (i.e., GCP implementation) and can be used to inform tailored interventions. Results Ten AHPs across six professions were interviewed. Participants identified both enablers and barriers to implementing GCP across nine domains of the TDF and enablers across three additional domains. Examples of enablers included strong beliefs about the importance of GCP in increasing research rigour and participant safety (i.e. from TDF - beliefs about consequences); applying clinical skills and personal attributes when implementing GCP (i.e., skills), available training and support (i.e., environmental context and resources); and alignment with their moral sense to 'do the right thing' (i.e., professional identity). Barriers to GCP implementation were generally less commonly reported but included reduced time to implement GCP and a sense of 'red tape' (i.e., environmental context and resources), a lack of knowledge of GCP principles (i.e., knowledge) and a fear of making mistakes (i.e., emotions), and varying relevance to individual projects (i.e., knowledge). Suggestions for support were identified beyond training, such as physical resources (e.g., prescriptive checklists, templates and scripts), additional time, and regular one-on-one mentoring support. Conclusion Findings suggest that while clinicians recognise the importance of GCP and want to implement it, they report barriers to its practical implementation. GCP training alone is unlikely to address these barriers to implementing GCP in daily practice. Findings suggest that GCP training may be more useful to AHPs when it is tailored to the allied heath context and supplemented with additional supports including check-ups from experienced researchers and access to prescriptive resources. Future research however is needed to investigate the effectiveness of such strategies.